Protostrongylid nematodes in caribou (Rangifer tarandus caribou) and moose (Alces alces) of Newfoundland - Lankester, Murray W.; Fong, David (Rangifer, 1998)
Two species of protostrongylid nematodes with dorsal-spined, first-stage larvae, are present in caribou and moose of Newfoundland. Elaphostrongyius rangiferi Mitskevich, 1958, a parasite introduced from Scandinavia, causes periodic epizootics of a severe neurological disease in caribou. Sick animals exhibiting signs of cerebrospinal elaphostrongylosis (CSE) were particularly noticeable in central Newfoundland each winter between 1981 and 1985. Those collected for examinarion were mostly male calves. The disease again became prominent in caribou on the Avalon Peninsula in the winters of 1996 and 1997; it may have spread to that isolated part of the province as recently as 1990. E. rangiferi was also found in moose but no cases of neurologic disease have been reported in this host. Parelapbostrongylus andersoni Prestwood, 1972, was found in caribou, both in central Newfoundland and on the Avalon Peninsula. Moose may also be infected. Of 1407 terrestrial gastropod intermediate hosts examined, 9 (0.6%) contained infective, third-stage, protostrongylid larvae resembling those of E. rangiferi and P. andersoni which are indistinguishable. The small dark slug, Deroceras laeve, dominated gastropod collections and was the only species infected.